STRATIGRAPHY OF THE CAPORALINO-SANT’ANGELO UNIT: A FAKE JURASSIC-EOCENE SUCCESSION OF THE “ALPINE” CORSICA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
This paper aims to provide new insights on the Caporalino-Sant’Angelo Unit outcropping north of Corte, in the Caporalino-Omessa area (NE Corsica). It belongs to the stack of the units from the “Alpine” Corsica, which overlies the “Hercynian” Corsica basement and its sedimentary cover. Based on a geological mapping, a refined lithostratigraphy and new datings, the Caporalino-Sant’Angelo Unit is a fake Middle Jurassic-Middle Eocene succession, sedimented on the European continental margin, because it is a Middle Eocene clastic wedge, accumulated in a synorogenic compressive basin located between the European distal continental margin and the deforming “Corsican” accretionary wedge. This basin received the siliciclastic input from the “Hercynian” Corsica basement, and the carbonatic input derived from the sedimentary cover of tectonic units, subsequently involved into the complex “Corsican” accretionary wedge.
Keywords: Stratigraphy; Clastic deposits; Calcareous nannofossils; Foraminifera; Eocene; Corsica; France